Sentencias por culpa patronal en accidentes de trabajo en Colombia. Una mirada desde la Seguridad y la Salud en el Trabajo (2021)
Employer's negligence for occupational accidents is a concept of jurisprudential and doctrinal origin, its sources are the civil liability of article 1604 of the Colombian Civil Code and the employer's negligence of article 216 of the Substantive Labor Code. The objective is to explore the decisions of the Supreme Court of Justice, Labor Cassation Chamber on occupational accidents with employer's negligence in the face of the minimum standards in hazards and risks management of the Occupational Health and Safety Management System. A documentary review of guilty verdicts for occupational accidents due to employer's negligence was carried out. Criteria: guilty verdicts due to employer's negligence in occupational accident, 2019-2020, Private Sector, Labor Cassation Chamber. An Excel matrix (Annex 1) was used as a collection instrument, 76 judgments were selected. A qualitative analysis was made in three phases: description, categorization and interpretation. The results showed in ratio decidendi considerations the employer failure to comply with the Occupational Safety and Health standards such as provision of personal protective equipment, diligence and care, omissive conduct, supervision of standards, safety protocols, training, safe tools and equipment. In conclusion, there was negligent and careless conduct, which showed that most of these severe and fatal occupational accidents occur because the employer did not take into account a preventive approach from the control and occupational hazards and risks management.